Potential heterogeneity in p53/S100B(ββ) complex - McDowell, Chester Dale (Kansas State University, 2012)
Intrinsically disordered proteins have been shown to be important in many physiological processes, including cell signaling, translation, and transcription. They are also associated with cancer, and neurodegenerative diseases. The tumor suppressor p53 contains several disordered regions, including the C-terminal negative regulatory domain (NRD). In cancer the function of p53 has been shown to be repressed by S100B(ββ) binding to p53-NRD. Binding of S100B(ββ) blocks acetylation and phosphorylation sites in the p53-NRD, which leads to tetramer dissociation and prevents p53 activation. NMR studies have shown that p53-NRD binds S100B(ββ) in a stable α-helix conformation. Interestingly, despite the well-converged and apparent rigid nature of the NMR structure ensemble, a majority of intermolecular NOEs used to calculate the NMR ensemble are very weak (≥6 Å). The final NMR structures also contains unsatisfied buried charged residues at the binding interface. It’s plausible that the p53-S100B(ββ) complex is more dynamic than previously believed. The goal of the study is to determine the potential conformational heterogeneity in p53-S100B(ββ) complex using molecular modeling. For this, five diverse structures were selected from the 40-member NMR ensemble. For each initial conformation, we performed 100 ns molecular dynamic simulations in explicit solvent to explore the structure and dynamics of the p53-NRD in complex with S100B(ββ). Several analytical tools were used to characterize the p53-NRD conformation, including root-mean squared deviation (RMSD), root-mean squared fluctuation (RMSF), and residue helicity. The accuracy of the simulations was mainly assessed by comparing with experimental NOEs. The results show that, even though the ensemble is heterogeneous it satisfies 82% of the experimental NOEs. Clustering analysis further suggests that many conformational sub-states coexist for this complex, and individual clusters appear to satisfy only subsets of NOE distances. Importantly, the buried surface analysis demonstrates that the heterogeneous ensemble generated from MD provides similar shielding of key residues, which include post-translational modification residues needed for p53 activation. This study also demonstrates that atomistic simulations can provide important insights into structure and dynamics of IDPs for understanding their biological function.
Keywords: Intrinsically Disordered Proteins; Molecular Dynamics; Biochemistry (0487)